Educação e patrimônio : a gênese de representações sociais sobre o Centro Histórico de Cuiabá por crianças - Cunha, Jeysson Ricardo Fernandes da (2024)
The present study aims to understand the child's relationship with the material, historical, and cultural aspects of the Historical Center of Cuiabá/MT, in order to investigate the production of meanings and the sharing of significances that contribute to the genesis of social representations within the peer group. The guiding axis of this study, therefore, concerns the analysis of the interrelations between childhood and heritage education with an emphasis on the Historical Center of Cuiabá/MT and how it is perceived, assimilated, interpreted, and appropriated by the involved children, in order to outline identity processes conferring meanings to social memories. The theoretical framework chosen for this study is based on Social Representations Theory (Moscovici, 1978; 2013; Jodelet, 2001; 2002) and the ontogenetic approach to social representations (Duveen, 1995; Castorina; Kaplan, 2003) in dialogue with the Cultural-Historical Theory (Vygotsky, 2006; 2009; 2010). Studies on collective and social memory (Halbwachs, 2003; Sá, 2015) contributed to the debate on the procedural construction of memory that marks experience in a close relationship with the past. These choices allowed for a psychosocial perspective of participatory Heritage Education (IPHAH, 2014), understanding the processes of social knowledge and human development in dialogue with culture and memory. The perspectives on the symbolic construction of the Historical Center according to Massey (2006; 2008), Searget (1981), Tuan (2005), and Jodelet (2005) complement the discussions. Also addressed are aspects related to the Geography of Childhood (Lopes; Vasconcelos, 2005), considering the existence of a spatial language of children. The methodological design of this study assumes a psychosocial perspective with qualitative emphasis, characterized by the understanding of socio-historical phenomena in the context of social relations, according to Gunther (2006). It is a single case study (Marková, 2017) on the relationship of children with the Historical Center of Cuiabá. Five children aged between seven and 12 participated in this study. Data were produced during a guided tour using a narrative script in the Historical Center of Cuiabá/MT. The children generated data using an action camera, and the data were processed using the qualitative analysis software ALTAS.TI and analyzed comprehensively. In general, the children in this study demonstrated that the Historical Center of Cuiabá was meaningful as a place for children—an open space for innovation, creativity, and unpredictability. They also revealed that the city is a space to be lived, understood, and that its tensions and conflicts are part of the reality to be faced with the participation of children. The interaction of the children showed that the Historical Center preserves testimonies of lived past and is a symbol of resilience in the present with the potential to create favorable conditions for the children's meaningmaking process. Through intergenerational dialogue, the city can foster forms of care, conservation, and appropriation as a metaphor for oneself and essential for effective democracy. The Heritage Education developed in this study through the narrative script proved to be a relevant pedagogical strategy by enabling the children's protagonism, simultaneously contributing to the exercise of citizenship, participation, and the right of children to the city.